The changing voices from a modern point of view (Journal of the College of Basic Education, 2023)
This research presents a linguistic phenomenon that affected and was affected by the different linguistic phenomena.When studying the grammatical, rhetorical, and morphological levels, we must look at what is called sounds.The changing (or ebb and flow sounds). The truth is that the ancients, from Hebron to Ibn Jinni,They gave it an explanation, interpretation, and description, and most of their opinions on it are still dependent on it to this day.